Measurement of unbalanced voltages in three-phase induction motors using acoustic transducers and zero-crossing-weighted energy - Lucas, Guilherme Beraldi [UNESP]; De Castro, Bruno Albuquerque [UNESP]; Alves, Brigite Peinado [UNESP]; Glowacz, Adam; Andreoli, Andre Luiz [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In modern industries, transducers and measurement systems have been largely applied for equipment monitoring. In this context, three-phase induction motors (TIMs) are the main focus of predictive maintenance due to their relevance within the production lines. Among electrical and mechanical failures in TIMs, voltage unbalance (VU) is a critical condition that can lead the motor to total failure. It motivated the development of sensor-based solutions to diagnose this supply anomaly, including the acoustic emission (AE) technique, which stands out as a non-invasive alternative for fault diagnosis. However, none of the previous works carried out a comprehensive evaluation of VU. Therefore, to fill this research gap, this manuscript proposes a detection, phase(s) identification, and percentage classification of VU. This approach is based on AE signals acquired by piezoelectric transducers and Zero-Crossing-Weighted Energy (ZE) to accomplish the analysis. The methodology consisted of several experiments where the TIM was subjected to unbalanced voltages. The signals were processed using the ZE index to perform a 3D clustering map for phase identification and a 2D linear regression for percentage classification. The results showed that the proposed method successfully evaluated the origin and magnitude of VU faults in TIMs.
Keywords: Acoustic Transducers; Fault Diagnosis; Voltage Unbalance; Wavelet Transform